Does Public Trust Encourage Voluntary Tax Compliance? A Study of Indonesian Taxpayers - Shelvi; Rachmawati, Tutik (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2025)
Indonesia continues to face persistent challenges in improving tax compliance. This study examines how public trust influences individuals’ willingness to voluntarily fulfill their tax obligations. A mixed-methods design was employed. Quantitative data were collected through structured questionnaires administered to 227 urban taxpayers, selected through purposive sampling based on recent tax compliance experience. Qualitative insights were drawn from in-depth interviews with selected participants to provide contextual understanding. Statistical analysis using PLS-SEM shows that trust in government has a significant and positive effect on voluntary tax compliance (path coefficient = 0.575, p < 0.01). Respondents were more likely to comply when they perceived tax revenues were used fairly and transparently. Interviews reinforced that fairness, transparency, and credible leadership are key elements that shape public trust. The findings suggest that building institutional trust is critical for long-term tax compliance. Policymakers need to shift away from coercive strategies and instead foster trust through transparent governance, equitable tax allocation, and consistent public communication. This study highlights the importance of behavioral and institutional factors in shaping tax morale in a middle-income country context